Risk of depression and anemia in users of hormonal endometriosis treatments: Results from the VIPOS study. (August 2020) - Moehner, Sabine; Becker, Kerstin; Lange, Jens A.; von Stockum, Sophia; Heinemann, Klaas
Abstract: Objective: Dienogest (DNG) 2 mg (Visanne) was launched for endometriosis treatment in Europe in 2010. The Visanne Post-approval Observational Study (VIPOS) was designed to assess the safety of DNG 2 mg/day compared to other hormonal endometriosis treatments, focusing especially on clinically relevant depression and anemia. Study design: Large, prospective, non-interventional, active surveillance study in six European countries. Participants were recruited via gynecologists or specialized centers routinely prescribing endometriosis medication. Self-administered questionnaires during study entry and follow-up collected information on baseline characteristics, health status and endometriosis treatment. Patient-reported anemia and depression cases were validated by health care professionals. Inferential statistics were based on Cox proportional hazards models and crude and adjusted hazard ratios (HR) between cohorts were calculated (including 95% confidence intervals [CI]). Adjustment for potential confounding was performed by including predefined prognostic factors as covariates in the Cox models. Results: Out of 26, 430 participants, 11.4% used DNG, 12.8% used other approved endometriosis medications (OAED) and 75.7% used hormonal treatments not approved but frequently used for endometriosis treatment (NAED). At baseline, DNG users more frequently reported a surgically confirmed endometriosis diagnosis, severe endometriosis-associated pain and a history of depression, compared to the other cohorts. Baseline characteristics showed large inter-country variability. Overall, the number of confirmed anemia and depression events were substantially lower than expected. The adjusted HRs for anemia were 1.1 (95% CI, 0.4–2.6) for DNG vs OAED and 1.3 (95% CI, 0.7–2.4) for DNG vs NAED. The adjusted HRs for new or worsening depression were 1.8 (95% CI, 0.3–9.4) for DNG vs OAED and 1.5 (95% CI, 0.8–2.8) for DNG vs NAED. Conclusion: The main limitations encountered (low number of confirmed events and considerable inter-country variability) made a robust statistical analysis and a solid interpretation of the results challenging. However, no safety signal regarding anemia for DNG users could be detected, whereas a slight increase in depression risk cannot be excluded but might be explained by baseline severity of endometriosis or unknown country-specific confounding variables. VIPOS reflected routine use of hormonal endometriosis medications and provided real-world insights into endometriosis management in Europe.